1999
DOI: 10.1103/physrevb.60.472
|View full text |Cite
|
Sign up to set email alerts
|

Doubling of the orbital magnetic moment in nanoscale Fe clusters

Abstract: Magnetic circular dichroism has been used to study the orbital and spin moments in supported nanoscale Fe clusters deposited in situ from a gas aggregation source onto highly oriented pyrolitic graphite in ultrahigh vacuum. Mass-filtered ͑2.4 nm, 610 atoms͒ and unfiltered ͑1-5 nm, 40-5000 atoms͒ clusters at low coverage have an orbital magnetic moment about twice that of bulk Fe. With increasing coverage the orbital moment of the unfiltered clusters converges to the bulk value. There is no detectable change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
85
4
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 22 publications
5
85
4
1
Order By: Relevance
“…On the other hand, the spin-orbit coupling splits the CF spin degenerate levels and a nonzero orbital moment contribution appears in the magnetic ground state. Usually the orbital moment is small compared to the spin component, but a remarkable enhancement of the orbital moment of magnetic systems was observed at film interfaces, 5 monoatomic metal chains, 6 nanoparticles, 7 or very small clusters. 8 In the limit of atomic size, that is, as atomic impurities in solids, the orbital moment may be only partially quenched, with values approaching the free atom ones.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the spin-orbit coupling splits the CF spin degenerate levels and a nonzero orbital moment contribution appears in the magnetic ground state. Usually the orbital moment is small compared to the spin component, but a remarkable enhancement of the orbital moment of magnetic systems was observed at film interfaces, 5 monoatomic metal chains, 6 nanoparticles, 7 or very small clusters. 8 In the limit of atomic size, that is, as atomic impurities in solids, the orbital moment may be only partially quenched, with values approaching the free atom ones.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive work [10][11][12][13][14][15][16][17][18][19] on magnetic surfaces and thin films has shown that a lowering of the symmetry results in an increase of m L compared to bulk systems, where the d-state hybridization and the crystal field effectively quench m L . This effect gives rise to a variety of interesting phenomena, such as enhanced and perpendicular magnetic anisotropy [2,[12][13][14][15][16]19].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 This excess was recently correlated to the augmentation of the orbital magnetic moment of the peripheral atoms. 10,11 Magnetic nanoparticles are also good candidates for the study of quantum effects in intermediate scales between the microscopic and the macroscopic classical world. 12,13 In real systems however, we usually deal with macroscopic ensembles of particles with different sizes and shapes.…”
Section: Introductionmentioning
confidence: 99%